A comparative study of pulsed dye laser versus long pulsed Nd:YAG laser treatment in recalcitrant viral warts. (4th July 2017) - Shin, Yo Sup; Cho, Eun Byul; Park, Eun Joo; Kim, Kwang Ho; Kim, Kwang Joong
Abstract: Background: Viral warts are common infectious skin disease induced by human papillomavirus (HPV). But the treatment of recalcitrant warts is still challenging. Objective: In this study, we compared the effectiveness of pulsed dye laser (PDL) and long pulsed Nd:YAG (LPNY) laser in the treatment of recalcitrant viral warts. Methods: We retrospectively analyzed the medical records of patients with recalcitrant warts treated with laser therapy between January 2013 and February 2016. Results: Seventy-two patients with recalcitrant warts were evaluated. Thirty-nine patients were treated with pulsed dye laser and thirty-three patients were treated with LPNY laser. The following parameters were used: PDL (spot size, 7 mm; pulse duration, 1.5 ms; and fluence, 10–14 J/cm 2 ) and LPNY (spot size, 5 mm; pulse duration, 20 ms; and fluence, 240–300 J/cm 2 ). Complete clearance of two patients (5.1%) in PDL group, and three patients (9.1%) in LPNY group were observed without significant side effects. The patients who achieved at least 50% improvement from baseline were 20 (51.3%) in PDL and 22 (66.7%) in LPNY, respectively. Conclusion: This research is meaningful because we compared the effectiveness of the PDL and LPNY in the recalcitrant warts. Both PDL and LPNY laser could be used as a safe and alternative treatment for recalcitrant warts.